Infective Endocarditis In A Patient With Ventricular Septal Defect And Patent Ductus Arteriosus - Sattwika PD., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Infective Endocarditis In A Patient With Ventricular Septal Defect And Patent DuctusArteriosus